Penggunaan Flashcard untuk Meningkatkan Hafalan Mufrodat dan Maharah Kitabah Bahasa Arab - Iffatunnisa, Fathina (Maliki Interdisciplinary Journal, 2024)
This study aims to explore the use of flashcards as a method to improve vocabulary memorization and writing skills in Arabic. The findings indicate that flashcards facilitate vocabulary retention and enhance the understanding of its usage in written contexts. The use of visuals and repetition through flashcards also significantly contributes to students’ writing abilities in Arabic. This research recommends flashcards as an interactive learning tool for Arabic language education.